2018
DOI: 10.1007/s42064-018-0020-0
|View full text |Cite
|
Sign up to set email alerts
|

Libration control of bare electrodynamic tether for three-dimensional deployment

Abstract: Various promising applications of electrodynamic tether have been proposed for space missions over the past decades. A crucial issue of these missions is to deploy an electrodynamic tether under a rapid and stable state. This paper aims to stabilize the libration motions of a bare electrodynamic tether during its three-dimensional deployment. The tethered system under consideration consists of a main-satellite and a sub-satellite connected to each other through a bare electrodynamic tether. A widely used dumbb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The spinning motion of E-sail was studied by Du et al, who concluded that tether flexible tether motion is an essential factor in the stability of spinning tether systems [21]. Electrodynamic forces provide a propellant-less source of energy for SEDT maneuvers and attract focus from scholars [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spinning motion of E-sail was studied by Du et al, who concluded that tether flexible tether motion is an essential factor in the stability of spinning tether systems [21]. Electrodynamic forces provide a propellant-less source of energy for SEDT maneuvers and attract focus from scholars [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Coefficient sat  should be relatively larger to attenuate disturbance. ( ) i fx is the hard saturation function, , i M S = indicates two saturation functions in(22)…”
mentioning
confidence: 99%
“…The study of Zhong shows that the libration dynamics and stability of EDT system is a key issue and regulated electric current in the tether to stable the libration motions [21]. Luo and Chen have developed the libration motions of EDT system by regular the tether current and length during the tether deployment [22], [23]. Li used a high fidelity multiphysics model of the EDT system for libration and transverse motion control of the system [24].…”
Section: Introductionmentioning
confidence: 99%